Collapse of Cylindrical Brushes with 2‐Isopropyloxazoline Side Chains Close to the Phase Boundary. Issue 7 (12th February 2013) - Bühler, Jasmin; Muth, Sandra; Fischer, Karl; Schmidt, Manfred
Abstract A high‐molar‐mass cylindrical brush polymer with a main chain degree of polymerization of Pw = 1047 is synthesized by free‐radical polymerization of a poly‐2‐isopropyloxazoline macromonomer with Pn = 28. The polymerization is conducted above the lower phase transition temperature of the macromonomer, i.e., in the phase‐separated regime, which provides a sufficiently concentrated macromonomer phase mandatory to obtain high‐molar‐mass cylindrical brushes. Upon heating to the phase transition temperature, the hydrodynamic radius is observed to shrink from 34 to 27 nm. Further increase in temperature resulted in aggregated chains which were observed to coexist with single chains until eventually only aggregates of μm size were detectable.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>